2007
DOI: 10.1016/j.bbrc.2006.12.106
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular signaling via ERK/MAPK completes the pathway for tubulogenic fibronectin in MDCK cells

Abstract: A classic in vitro model of branching morphogenesis utilizes the Madin-Darby canine kidney (MDCK) cell line. MDCK Strain II cells form hollow monoclonal cysts in a three-dimensional collagen matrix over the course of ten days and tubulate in response to hepatocyte growth factor (HGF). We and our colleagues previously showed that activation of the extracellular-signal regulated kinase (ERK, aka MAPK) pathway is necessary and sufficient to induce tubulogenesis in MDCK cells. We also showed in a microarray study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…It has previously been shown that fibronectin plays an essential role in the partial EMT that occurs early in the process of HGF-stimulated tubule formation. In addition, it has been previously shown that disrupting fibronectin expression impairs cyst growth and prevents the initiation of tubulogenesis in MDCK cells grown in 3D culture (16,26,47,50). Taken together, these findings suggest that proteins involved in remodeling the ECM play an important role in the development and expansion of multicellular epithelial structures in 3D culture.…”
Section: Discussionmentioning
confidence: 63%
“…It has previously been shown that fibronectin plays an essential role in the partial EMT that occurs early in the process of HGF-stimulated tubule formation. In addition, it has been previously shown that disrupting fibronectin expression impairs cyst growth and prevents the initiation of tubulogenesis in MDCK cells grown in 3D culture (16,26,47,50). Taken together, these findings suggest that proteins involved in remodeling the ECM play an important role in the development and expansion of multicellular epithelial structures in 3D culture.…”
Section: Discussionmentioning
confidence: 63%
“…42 Blockade of the Mek-dependent pathway of ERK activation with PD98059 significantly reduced the biologic effects of MSP on TEC, suggesting the involvement of this pathway in MSP/RON signal transduction as previously shown for tubulogenesis induced by MET receptor activation. 27,[43][44][45] Apart from the inhibition of apoptosis, MSP preserved the expression of several molecules involved in physiologic tubular functions. Indeed, in cisplatin-treated TEC, MSP maintained the ability to internalize albumin and the expression of the endocytic receptor megalin that is essential for protein reabsorption.…”
Section: Discussionmentioning
confidence: 99%
“…In these cells, the kinase activity of Raf was induced using an estrogen analog, 4-hydroxytamoxifen (4-HT) (Sigma), at a concentration of 1 M as described previously (25,26).…”
Section: Methodsmentioning
confidence: 99%